(untitled) (Eurasian Medical Research Periodical, 2022)
This article provides information on the prevalence and epidemiology of pancreas cancer in the Bukhara region. The data was taken on the contingent of patients with malignant neoplasms of the pancreas registered in oncological institutions of the Bukhara region in 2021.